Roller sammying machine with controlled drive of working rollers - Amanov, Auezhan; Bahadirov, Gayrat; Nabiev, Ayder; Tsoy, Gerasim; Abdullajonov, Asrorbek (Edelweiss Applied Science and Technology, 2026)
The objective of this study is to improve mechanical fluid removal from semi-finished leather products to reduce harmful vapor emissions during drying and enhance moisture uniformity across hide topography. An improved roller machine is proposed, incorporating a combined toothed-chain transmission to synchronize the angular velocities of the driving and driven rollers while adapting to material thickness. A kinematic analysis of the drive system is conducted, and analytical expressions for linear velocity, acceleration and angular velocity of moving links are derived. The analysis confirms equal linear velocities at the roller contact points, ensuring stable compression and uniform fluid extraction. The adaptive drive mechanism maintains consistent roller motion despite variations in hide thickness, promoting more efficient and even moisture removal. The proposed roller machine design enables controlled mechanical dewatering of hides, minimizing reliance on heat drying and thereby reducing the release of hazardous tanning vapors. The results provide a theoretical basis for designing roller systems in fibrous material processing machines, supporting optimized loading modes that achieve reliable fluid removal and improved environmental performance in leather production.